Autolytic hydrolases affect sexual and asexual development of Aspergillus nidulans - Emri, Tamás; Vékony, Viktória; Gila, Barnabás; Nagy, Flóra; Forgács, Katalin; Pócsi, István (Folia microbiologica, 2018)
Radial growth, asexual sporulation, and cleistothecia formation as well as extracellular chitinase and proteinase formation of Aspergillus nidulans were monitored in surface cultures in order to study the physiological role of extracellular hydrolase production in carbon-stressed cultures. We set up carbon-stressed and carbon-overfed experimental conditions by varying the starting glucose concentration within the range of 2.5 and 40 g/L. Glucose starvation induced radial growth and hydrolase production and enhanced the maturation of cleistothecia; meanwhile, glucose-rich conditions enhanced mycelial biomass, conidia, and cleistothecia production. Double deletion of chiB and engA (encoding an extracellular endochitinase and a β-1,3-endoglucanase, respectively) decreased conidia production under carbon-stressed conditions, suggesting that these autolytic hydrolases can support conidia formation by releasing nutrients from the cell wall polysaccharides of dead hyphae. Double deletion of prtA and pepJ (both genes encode extracellular proteases) reduced the number of cleistothecia even under carbon-rich conditions except in the presence of casamino acids, which supports the view that sexual development and amino acid metabolism are tightly connected to each other in this fungus.
Keywords: Peptide Hydrolases; regulace genové exprese u hub; glukosa; regulace genové exprese enzymů; hydrolasy; Aspergillus nidulans; proteasy; vývojová regulace genové exprese; hyfy; Spores, Fungal; mutace; celulasa; fungální proteiny; spory hub; chitinasy; Gene Expression Regulation, Developmental; Chitinases; Hydrolases; Hyphae; Fungal Proteins; Mutation; Gene Expression Regulation, Enzymologic; kultivační média; Cellulase; Gene Expression Regulation, Fungal; Glucose; Culture Media